Factors Affecting the Integration of Dental Services Into Health and Social Care for People With Complex Needs - Afsha Musa; Joelle Booth; Hannah Wheat; Robert Witton; Martha Paisi (Health Expectations)
ABSTRACT Background People with complex social and medical needs require a high level of support and face multiple barriers in accessing health and social care services. With limited access to dental care, their high oral health needs go largely unaddressed. Integration of oral healthcare into primary care, alongside improved cross‐sector working, has been advocated to bring together services across the system to achieve oral health equity. Aim To explore the factors affecting integration of dental services into health and social care for people with complex needs. Methods A qualitative research study was undertaken across two sites in the southwest of England, involving pathways designed to address the oral health needs of those with complex needs. Semi‐structured interviews took place with three groups: patients with experience of each pathway, service providers and community support staff. These interviews were analysed through reflexive thematic analysis. Results Forty‐two individuals (15 males and 27 females) agreed to participate in the study. Key themes included (i) the need for services to be co‐developed according to population need, (ii) for service coordination to be managed by a central hub, (iii) the important role of support workers and (iv) the requirement for collaboration between organisations to develop multi‐agency pathways of communication. Conclusion The objectives of integration should be addressed at all stages of service planning from design to delivery of the pathway. To develop integrated dental care pathways, it is recommended that a codesign approach is used harnessing community expertise, patient experience and the involvement of all service providers in the planning process. Patient and Public Involvement Statement The authors were guided by the Peninsula Dental Social Enterprise Community Clinic Patient and Public Involvement (PPI) group, which includes people with lived experience of complex social and medical needs and those supporting them, who meet twice yearly as a focus group. The group explored aspects of the services offered to this cohort to aid the identification of research aims and outcomes for the study. Further to this, the original interview guides were reviewed and edited by a community link worker.